Metabolic syndrome in relation to dietary acid load: a dose–response meta-analysis of observational studies - Al-Hawary, Sulieman Ibraheem Shelash; Mushabab, Faris; Abullais, Shahabe Saquib; Althomali, Raed H.; Saleh, Ebraheem Abdu Musad; Alnajjar, Serar Nassir; Oudaha, Khulood H.; Romero-Parra, Rosario Mireya; Hussien, Beneen M.; Garousi, Nazila (Frontiers in Nutrition, 2023)
Background and aim: Several studies have identified that diet-induced mild metabolic acidosisdietary acid load (DAL) may be associated with the risk odds of metabolic syndrome (MetS); although evidence is inconclusive. This dose-response meta-analysis aimed to examine the relation of dietary acid load (DAL) with to MetS.Methods: A systematic literature search was carried out in PubMed and Scopus up to April 2023 for pertinent studies evaluating the relation of DAL scores, including potential renal acid load (PRAL) and net endogenous acid production (NEAP), to the odds risk of MetS. The odds ratios (OR) with 95% confidence intervals (CI) were pooled using a random-effects metaanalysis to test the association.Results: A total of 8 studies, with an overall sample size of 31,351 participants, were included in this meta-analysis. Higher DAL scores were significantly related to the elevated odds risk of MetS (NEAP: OR = 1.42, 95%CI = 1.12 -1.79; PRAL: OR = 1.76, 95%CI = 1.11-2.78), with a significant evidence of heterogeneity across studies. The linear dose-response analysis proposed that a 10 mEq/day elevation in NEAP and PRAL was linked to a 2% (OR = 1.02, 95%CI = 1.001 -1.05) and 28% (OR = 1.28, 95%CI = 1.11 -1.47) increased odds risk of MetS, respectively. No nonlinear association was observed between MetS and NEAP (Pnonlinearity = 0.75) and PRAL (P-nonlinearity = 0.92).This study revealed a significant direct relationship between DAL and MetS.Therefore, lower acidogenic diets are suggested for the prevention of MetS.